VIDA XR: Mixed Reality Tool for teaching anatomy to dental students - Silva, Izabela Marina Ferreira da; Arcanjo, Emilly da Silva; Ramos, Lucas Carvalho; Macedo, Mary Caroline Skelton; , Laila Gonzales Freire; Maltarollo, Thalya Fernanda Horsth; Tori, Romero; Nakamura, Ricardo (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2025)
Teaching dental anatomy faces challenges related to ethical concerns, cost of materials and quality of artificial representations. Virtual and augmented reality technologies have been explored for education and training in healthcare for the same motivations. In this paper we present a novel mixed reality tool that allows dental students to visualize and manipulate 3D models of tooth surface and tooth root, generated from microtomography scans. The development process by a multidisciplinary team is described, followed by results from performance evaluation and assessment by an expert panel. Performance was within the guidelines for applications in the adopted head-mounted device, and expert assessment was positive regarding its usefulness and ease of use. Future work includes assessing the tool’s pedagogical effectiveness in anatomy classes.